2019
DOI: 10.3389/fphys.2019.00843
|View full text |Cite|
|
Sign up to set email alerts
|

Supervised Physical Training Enhances Muscle Strength but Not Muscle Mass in Prostate Cancer Patients Undergoing Androgen Deprivation Therapy: A Systematic Review and Meta-Analysis

Abstract: Introduction: Androgen deprivation therapy (ADT) is considered the basic treatment for advanced prostate cancer, but it is highly associated with detrimental changes in muscle mass and muscle strength. The aim of this meta-analysis was to investigate the effects of supervised physical training on lean mass and muscle strength in prostate cancer patients undergoing ADT. Methods: A systematic literature search was performed using MEDLINE, Embase, and ScienceDirect until October… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
36
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(38 citation statements)
references
References 64 publications
2
36
0
Order By: Relevance
“…Testosterone levels are typically reduced to castrate levels, and the loss of lean mass has typically ranged between − 2 and − 4% per year [ 77 ], consistent with the findings described previously in transgender women. A recent meta-analysis concluded that exercise interventions including resistance exercise were generally effective for maintaining muscle mass and increasing muscle strength in prostate cancer patients undergoing androgen deprivation therapy [ 94 ]. It is important to emphasize that the efficacy of the different training programs may vary.…”
Section: Discussionmentioning
confidence: 99%
“…Testosterone levels are typically reduced to castrate levels, and the loss of lean mass has typically ranged between − 2 and − 4% per year [ 77 ], consistent with the findings described previously in transgender women. A recent meta-analysis concluded that exercise interventions including resistance exercise were generally effective for maintaining muscle mass and increasing muscle strength in prostate cancer patients undergoing androgen deprivation therapy [ 94 ]. It is important to emphasize that the efficacy of the different training programs may vary.…”
Section: Discussionmentioning
confidence: 99%
“…The terms used were: 'prostate cancer' and 'resistance training' in association with a list of sensitive terms (Supplementary Material Table S1). In addition, we also performed a manual search of the reference lists provided in the selected papers as well as previous systematic reviews and meta-analytic studies in patients with prostate cancer [14][15][16][17][18][19] to detect studies potentially eligible for inclusion.…”
Section: Study Selection Proceduresmentioning
confidence: 99%
“…This is important given the role of resistance exercise to counter treatment-related toxicities in men with prostate cancer [2,12]. Furthermore, despite several systematic reviews examining exercise effects in prostate cancer patients [14][15][16][17][18][19], none have addressed the minimal exercise dosage required for improvements in common patient-reported outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…A possible explanation for such discrepancy may be related to testosterone suppression. In fact, testosterone is the most important androgen that controls muscle protein synthesis; thus, in such patients the muscle growth induced by intensive training is abolished too [64].…”
Section: Physical Activity and Androgen Deprivation Therapy-related Tmentioning
confidence: 99%